Body 2.0 : the engineering revolution in medicine - Latta, Sara L. (Twenty-First Century Books, 2020)
Discusses advancements in improving the health and function of the human body through bioengineering, prosthetics, and gene editing. Covers lab-grown organs, designer drug development, and how to pursue a career in the industry. Includes photographs, sidebars, a glossary, an index, and resources for further research.